PELAKSANAAN PERLINDUNGAN ANAK TERHADAP KEKERASAN DI LINGKUNGAN SEKOLAH BERDASARKAN UNDANG-UNDANG NO. 35 TAHUN 2014 - Diah Indah Novianti (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT DIAH INDAH NOVIANTI (13.11.1001.1011.243), "Implementation of Child Protection against Violence in School Environment Based on Law no. 35 Year 2014 ". Under the guidance of Kunti Widayati, S.H., M.Hum as mentors l and H. Syamsudin, S.H., M.Hum as mentors ll.The research is intended to find out the factors affecting the maltreatment of pupils conducted by the teacher and to find out the effort to overcome the maltreatment of the students conducted by the teacher in School Area in Samarinda City.This research is located at SMP Negeri 35 Samarinda. The research method used is Approach Method, Legal Material, Data Collection Technique and Data Analysis. In the field research the authors held direct interviews with teachers BK in SMP Negeri 35 Samarinda. This study then produced primary data and secondary data, then deductively and, presented descriptively.The result of the research shows that the factors that cause student abuse are done by the teacher in the school are: the student factor itself, the teacher factor, the educational system factor and the culture of the society itself. Lack of teacher awareness to solve the problem by deliberation.Efforts taken to tackle student abuse by teachers in the school environment in Samarinda include: Prosecution of legal proceedings for perpetrators of violent crimes against children, processing of suspects in accordance with applicable rules, severe penalties or sanctions for suspects, Held coaching both in the school environment and in the community, legal counseling to teachers and the community and provide an understanding of the importance of muasyawarah in solving problems.